Parents' perceptions on social and economic life skills of adult children with mental retardation - Shieh, Jiunn-Yeong (Michael) (Animo Repository, 2003)
This study determines the perceptions of parents of children with mental retardation (CWMR) about social and economic life skills needed by them. It finds out if there was any significant difference between the social and economic life skills needed and the extent to which they were addressed, as perceived by the parents. Fifty-one parents of children with mental retardation were administered a validated researcher-made questionnaire. Percentages, weighted means and t-test were the statistical tools employed to test the data gathered. T-test determined the significant difference between the parents' perceived needed social and economic life skills and addressed social and economic life skills. Parents perceived that CWMR needed all the life skills along (3.92 overall mean score) the areas of employment, employment setting (3.75) education and training (3.73) financial management (3.45) family life (3.47) leisure pursuits (3.66) community involvement (3.36) and personal relationsip and responsibilities (3.79). It was also found in this study that the need for all the life skills along (3.22 overall mean score) the areas of employment, employment setting (3.33) education and training (3.33) financial management (2.93) family life (3.14) leisure pursuits (3.29) community involvement (2.92) and personal relationship and responsibilities (3.41) are addressed by the schools that the CWMR attend. It was also found out that there is a difference between the needed skills and the extent of provision of such as perceived by the parents. On the life skills, such areas as employment, employment setting, education and training, financial management, family life and leisure pursuits, community involvement and personal responsibilities and relationships, the computed t-values were all significant ( p < .05). There is a significant difference between the parents perceptions on the life skills needed by their CWMR and those relating to how the schools address the need for these life skills. The parents' expectations in terms of the needs of their CWMR do not seem to match the extent to which the schools provide these children to address their need for adulthood life skills.